Review of finance and investment in disaster resilience in the built environment - Adeniyi, Onaopepo; Perera, Srinath; Collins, Andrew (International Journal of Strategic Property Management, 2016)
In stark comparison to reductions achieved in the number of human casualties from disasters it is now evident that economic losses are increasing at a much higher rate. While several events contribute to economic loss from disasters, loss from built environment (property) damages and its consequential effects are significant. The overarching purpose of this paper is to systematically summarise and synthesise literature, critically discuss issues, and identify methodological problems as well as research, practice gaps and potential solutions to matters relating to financing and investment in Disaster resilience in the Built Environment. Literature materials used for this the paper were gathered from reputable sources. As part of the findings of the study, a growing shift towards investment and enhancement of disaster resilience through the principles of corporate social responsibility and public private partnership was observed. However, many of the documented investments were made after disaster struck once or nearby.